Upper Midwest tribal natural resource managers' perspectives on chronic wasting disease outreach, surveillance, and management. Issue 7 (16th May 2022) - Schwabenlander, Marc D.; Potts, Nicole; Moore, Seth; Larsen, Peter A.; Bernstein, Lauren A.; Wolf, Tiffany M.
Abstract: Management strategies for chronic wasting disease (CWD) across tribal lands have varied in response to changing dynamics of CWD risk. As CWD continues to spread across the United States, concerns associated with the disease are increasing. We interviewed 19 natural resource managers representing Anishinaabe and Dakota tribes in Minnesota, Michigan, and Wisconsin with goals of understanding needs and opportunities for CWD engagement, surveillance, and outreach on tribal lands; the implementation of natural resources policy and management across tribal nations; and opportunities for tribal partnership‐development to control CWD. Qualitative data analyses of interview responses revealed substantial variation in the number of tribal hunters, hunter regulation, and huntable tribal lands across our study area. Proximity of tribal lands in relation to CWD detections impacted tribal agency management strategies for CWD. Our results indicate a desire for CWD outreach and surveillance, mutually beneficial collaborations, and a need for incorporating cultural knowledge into CWD management strategies. We conclude that tribal CWD management and surveillance plans will be enhanced through strategic and thoughtful CWD outreach methods. Moreover, partnerships must recognize tribal sovereignty and respectfully integrate tribal values, knowledge, and worldview.